1998
DOI: 10.1007/bf01451055
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of ankylosing spondylitis and undifferentiated connective tissue disease

Abstract: We report the case of a 45-year-old Caucasian woman suffering from ankylosing spondylitis and undifferentiated connective tissue disease in whom the prevailing clinical features were retinal vasculitis and inflammatory low back pain. HLA typing revealed the concomitant presence of B27 and DR2 antigens. We hypothesise that the uncommon coexistence of ankylosing spondylitis and connective tissue disease in the same patient could be due to the exceptional association of HLA- B27 with the DR2 antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Several reports on retinal vasculitis in HLA-B27-positive patients were previously published and were considered a part of atypical posterior segment manifestations in HLA-B27-associated uveitis. 2,[4][5][6][7][8][9] From a cohort of 166 patients with HLA-B27-associated uveitis, Rodriguez et al reported 7 (4%) patients with retinal vasculitis, which is in accordance with our findings. 4 The occurrence of retinal vasculitis in HLA-B27-associated disease may in fact even be higher than 3%, as not all our patients with retinal vasculitis were tested for HLA-B27.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several reports on retinal vasculitis in HLA-B27-positive patients were previously published and were considered a part of atypical posterior segment manifestations in HLA-B27-associated uveitis. 2,[4][5][6][7][8][9] From a cohort of 166 patients with HLA-B27-associated uveitis, Rodriguez et al reported 7 (4%) patients with retinal vasculitis, which is in accordance with our findings. 4 The occurrence of retinal vasculitis in HLA-B27-associated disease may in fact even be higher than 3%, as not all our patients with retinal vasculitis were tested for HLA-B27.…”
Section: Discussionsupporting
confidence: 91%
“…8 Until now, less than 35 HLA-B27-positive patients with retinal vasculitis have been reported. 2,[4][5][6][7][8][9] However, these patients were not thoroughly studied and their clinical and FA characteristics were not well described. Although Yalçindag et al published a case report on occlusive retinal vasculitis in an HLA-B27-positive patient, in other cohorts no retinal vascular occlusions or the development of neovascularizations were found in their cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation